Study on location of cerebral lesion among patients with hemorrhagic cerebrovascular accident - Chakraborty, Nabanita; Banani Kundu; Soham Chakraborty; Prabir Kumar Kundu (Asian Journal of Medical Sciences, 2024)
Background: In hemorrhagic cerebrovascular accident, bleeding occurs directly into the brain parenchyma. Intracerebral hemorrhage usually occurs at certain sites in the brain, i.e., thalamus, putamen, cerebellum, and brain stem. The surrounding area of brain may be damaged by pressure produced by the mass effect of the hematoma. Increase in intracranial pressure occurs. Aims and Objectives: The aim and objective of the study are to compare the localization of cerebral lesions with the frequency of intraventricular hemorrhage and to study the prognosis of hemorrhagic cerebrovascular accident (CVA) as per its anatomical location in computed tomography (CT) scan. Materials and Methods: One-year observational cross-sectional study was conducted in 60 patients with CT scan diagnosed hemorrhagic CVA. Results: Regarding the site of the hemorrhagic CVA, the most commonly affected area was basal ganglia (46.7%) followed by thalamus (18.3%); other areas include pons (8.3%), paraventricular (8.3%), cerebellar (6.7%), lobar (5%), internal capsule (3.3%), and intraventricular (3.3%). Conclusion: This study reflects a spectrum of cerebral location of hemorrhagic stroke which may help in the management of hemorrhagic CVA patients.